Gold(i)-catalyzed highly stereoselective synthesis of polycyclic indolines: the construction of four contiguous stereocenters. Issue 2 (30th October 2015) - Yang, Jin-Ming; Li, Peng-Hua; Wei, Yin; Tang, Xiang-Ying; Shi, Min
Abstract : A convenient and efficient synthetic method has been developed to construct highly functionalized polycyclic indoline skeletons with four contiguous stereocenters. Abstract : A convenient and efficient synthetic method has been developed to construct highly functionalized polycyclic indoline skeletons with four contiguous stereocenters, which are of great importance in biological and pharmaceutical chemistry. The selective formation of either the oxabridged-ring or ring-opening polycyclic indoline derivatives can be controlled by using different gold catalytic systems. A variety of polycyclic indoline derivatives were obtained in moderate to good yields under mild conditions with moderate to excellent enantioselectivity.